2020
DOI: 10.3389/fendo.2020.00575
|View full text |Cite
|
Sign up to set email alerts
|

Guizhi Fuling Wan, Chinese Herbal Medicine, Ameliorates Insulin Sensitivity in PCOS Model Rats With Insulin Resistance via Remodeling Intestinal Homeostasis

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disease with reproductive dysfunction and metabolic disorder in women of childbearing age. Gastrointestinal microbiome contributes to PCOS through mediating insulin resistance. Guizhi Fuling Wan, Chinese herbal medicine, can treat PCOS with insulin resistance (PCOS-IR), but the underlying mechanism is not clear. The aim of this study was to characterize the exact mechanism of Guizhi Fuling Wan action and whether it is related to the regulation of intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 45 publications
3
36
0
1
Order By: Relevance
“…However, Ruminococcaceae_UCG-014 has not been reported. In addition, differences between Lachnospiraceae UCG-008 and Lachnospiraceae_NC2004_group were also revealed at the animal level [19,20]. Therefore, a certain correlation exists between the current research and our results, and the latter can be used as a supplement to study the gut microbiota of PCOS.…”
Section: Discussionsupporting
confidence: 60%
“…However, Ruminococcaceae_UCG-014 has not been reported. In addition, differences between Lachnospiraceae UCG-008 and Lachnospiraceae_NC2004_group were also revealed at the animal level [19,20]. Therefore, a certain correlation exists between the current research and our results, and the latter can be used as a supplement to study the gut microbiota of PCOS.…”
Section: Discussionsupporting
confidence: 60%
“…After treatment with β-sitosterol, the structure of the gut microbiota in the PCOS group was significantly changed. Zhu et al ( 28 ) found that the relative abundance of Alloprevotella was decreased significantly in PCOS. However, Bacteroidete-Alloprevotella and Ambiguous_taxa-Alloprevotella were upregulated by β-sitosterol administration, whereas Firmicutes-Lactobacillus, Bacteroidetes-f_Muribaculaceae_ASV_4 , and f_Muribaculaceae_ASV_16 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that traditional Chinese medicine can improve metabolic disorders by regulating the composition and functional structure of the gut microbiota ( 27 ). For example, Guizhi Fuling Wan as a Chinese herbal medicine could control inflammation by regulating the gut microbiota, and had a certain therapeutic effect on PCOS ( 28 ). This study aimed to explore whether the effect of β-sitosterol in BSYXF on PCOS-like mice is achieved by gut microbiota, so as to provide new therapeutic targets for the treatment of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulating researchers realized that the gut dysbacteriosis is inextricably linked to the onset of the chronic inflammatory diseases, especially PCOS (Insenser et al, 2018;Torres et al, 2018). A large number of animal studies have confirmed the alternation of gut microbiome in PCOS, including a decline in α diversity and the alternation in β diversity (Wang et al, 2020c;Zhu et al, 2020). In clinical studies, females with PCOS also shown extremely different intestinal microbiome compared to healthy controls (Eyupoglu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%